B. N. RECKITT: The lindley Affair. A Diary of the Boer War - Bouch, R.J. (Scientia militaria : South African journal of military studies, 2012)
On May 31, 1900, the 13th Battalion Imperial Yeomanry surrendered to General Piet de Wet at Lindley in the north-eastern Free State.The author has here published the diary of his father, a trooper involved in the 'Lindley Affair: and supplemented it with outlines of the causes and course of the Second Anglo- Boer War, along with three chapters examining the encounter from both sides and critically evaluating the episode with a view to determining responsibility for the surrender. The well-written diary, although dealing with a relatively insignificant encounter, has merit in its detailed exposition of life in the 13th during the six days of fighting which preceded the surrender. One receives an admirably clear picture of activities both in the command sector and amongst the men.